2018
DOI: 10.1097/qad.0000000000001939
|View full text |Cite
|
Sign up to set email alerts
|

Daily or on-demand oral tenofovir disoproxil fumarate/emtricitabine for HIV pre-exposure prophylaxis

Abstract: Most PrEP users were high risk MSM and opted for on demand PrEP. PrEP use was associated with a low HIV incidence and a high rate of condomless sex with a modest increase in bacterial STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 22 publications
11
27
3
1
Order By: Relevance
“…We were able to recruit a large sample of PrEP users to comprehensively investigate the extent of informal PrEP use and associated factors. The recruited population is similar to previously published studies regarding age, a high number of sexual partners and low condom use . Surveys from France and Australia reported informal PrEP use predominantly in younger populations , which might be due to recruitment differences.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We were able to recruit a large sample of PrEP users to comprehensively investigate the extent of informal PrEP use and associated factors. The recruited population is similar to previously published studies regarding age, a high number of sexual partners and low condom use . Surveys from France and Australia reported informal PrEP use predominantly in younger populations , which might be due to recruitment differences.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the type of PrEP use, previous studies in Belgium, the Netherlands and Australia found that between 23.5% and 48% of the participants preferred non-daily PrEP [12,[28][29][30][31]. A single-centre study in France found the preference for on-demand PrEP to be as high as 75.6% [9]. In our study, we found the proportion of on-demand/intermittent PrEP users to be on the lower end of this spectrum (23.9%).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the number of condomless anal sex acts with casual partners increased over time, whereas the number of partners and sex acts were stable . Also in France, the rate of condomless sex at last intercourse increased from 53.3% at baseline to 79% at month 12 . In the light of prevention‐effective adherence, the terminology of “risk taking” and hence its assessment may no longer be appropriate for HIV.…”
Section: Discussionmentioning
confidence: 63%
“…The majority of previous studies reported on situations in which event‐driven PrEP was only a hypothetical option , and where stops were associated with daily adherence problems and reduced risk . Data on actual choices between daily and event‐driven PrEP among MSM are only available from three studies in the European setting, the roll‐out programme in France , the Be‐Prepared study in Belgium , and our own study, the Amsterdam PrEP (AMPrEP) demonstration project in the Netherlands . Mainly quantitative data have been reported from these settings up to now related to choices between PrEP‐regimens.…”
Section: Introductionmentioning
confidence: 99%